SKI Expression Suppresses Pathogenic Th17 Cell Response and Mitigates Experimental Autoimmune Encephalomyelitis - Li, Ping; Guo, Zengli; Wan, Yisong Y. (Frontiers in Immunology, 2021)
Pathogenic Th17 cells are critically involved in many autoimmune diseases, while non-pathogenic Th17 cells are more immune regulatory. Understanding the mechanisms of the induction and maintenance of pathogenic Th17 cells will benefit the development of therapeutic treatments of related diseases. We have shown that the transforming growth factor-β (TGFβ) induced SKI degradation and dissociation from Smad4 complex is a prerequisite for TGFβ-induced Th17 cell differentiation. However, it is unclear whether and how SKI regulates pathogenic Th17 differentiation, which does not require TGFβ cytokine. Here we showed that SKI expression was downregulated during pathogenic Th17 cell differentiation and the ectopic expression of SKI abrogated the differentiation of pathogenic Th17 cells. Functionally, using a knock-in mouse model, we found ectopic SKI expression specifically in T cells prevented myelin oligodendrocyte glycoprotein peptide (MOG33-55) induced experimental autoimmune encephalomyelitis (EAE), an animal model of human multiple sclerosis. We further revealed that induced SKI expression in already differentiated pathogenic Th17 cells reduced the maintenance of Th17 program and ameliorated EAE in an adoptive T cell transfer model. Therefore, our study provides valuable insights of targeting SKI to modulate pathogenic Th17 cell function and treat Th17-related diseases.